Dermoid Cyst of the Lateral Neck Included Within the Submandibular Gland. Issue 1 (January 2016) - Kusuyama, Yukiko; Takeuchi, Noritami; Wakabayashi, Ken; Yura, Yoshiaki
Abstract : Abstract: Dermoid cysts are benign lesions of congenital origin, and those in the head and neck region are usually present as a midline neck mass. They rarely appear in the lateral neck. This article describes the clinical presentation and histopathologic features of an extremely rare case of lateral dermoid cyst included within the submandibular gland in a 58-year-old man. The etiology of the cyst is also discussed.